Optimum Portfolio Selection using a Hybrid Genetic Algorithm and Analytic Hierarchy Process: An Application to Amman Stock Exchange (Global Journal of Management and Business Research, 2021)
The aim of this study is to investigate the ability of a hybrid genetic algorithm (HGA) and analytic hierarchy process (AHP) in selecting the optimum portfolio. This of course, helps investors to decide the most appropriate investment alternatives. For that purpose, the study creates portfolios using daily returns of the companies listed in Amman Stock Exchange, for the period from January 1, 2015 to December 31, 2015. The results show that HGA can identify portfolios that are in the efficient frontier.HGA has more advantages than disadvantages for the portfolio selection cases in which the scale of the problem or the nonlinear constraints cannot be solved by linear or quadratic models. In addition, the results reveal that AHP can select the optimum portfolio among the portfolios obtained by HGA.
Keywords: hybrid genetic algorithm; analytic hierarchy process; portfolio selection